The Multiple Roles of B Lymphocytes in the Onset and Treatment of Type 1 Diabetes: Interactions between B Lymphocytes and T Cells - Yangfan Xiao (Hindawi Limited, 2021)
Although type 1 diabetes is thought to be an organ-specific autoimmune disease, mediated by effective CD4+ and CD8+ T cells, it has recently become clear that B cells participate in the initiation and progress of this disease. Indeed, B cell deletion can prevent or reverse autoimmune diabetes in nonobese diabetic mice and even result in partially remaining β cell function in patients with new-onset type 1 diabetes. This review summarizes the dual role of B cells in this process not only of pathogenic effect but also of immunoregulatory function in type 1 diabetes. We focus on the impact that B cells have on regulating the activation, proliferation, and cytokine production of self-reactive T cells along with regulatory T cells, with the aim of providing a better understanding of the interactions between T and B cells in immunopathogenesis and improving the efficacy of interventions for clinical practice.